Urban green spaces: a necessity for the health and well-being of the inhabitants, the case of Biskra - Benmechiche, Meriem; Bennacer, Leila; Kassah Laouar, Ines (Journal of Human Sciences, 2021)
Urban nature is a crucial theme that requires everyone’s interest. Massive and extensive urbanization for the benefit of natural and green spaces has given rise to degraded urban spaces, particularly from an environmental point of view. As a result, awareness of this situation has led cities to rethink their organization and priorities. Parks and gardens around the world have become the structuring element of their cities and regions, in addition to their effect on the urban environment, they play several roles and present several solutions: leisure, educational and meeting spaces. , relaxation, practice of sport… etc. In Algeria, most of the existing gardens date from the colonial era. The town of Biskra is an example, its two important gardens Landon and 5juillet1962 inherited from the colonial era are a very precious green heritage. With a large vegetation cover, they must be carefully managed and preserved.